Álvaro Cunqueiro, Néstor Luján and Family - Adolfo Sotelo Vázquez (Abriu: Estudos de Textualidade do Brasil, Galicia e Portugal, 2012)
The aim of this article is to document and date, in detail, the relations between Cunqueiro and distinguished Catalan intellectuals in the 1950s and 1960s from memorial texts, news in journals and authors’ testimonies. Thus we can establish the chronology of these contacts and follow the reception of Cunqueiro’s work and personality in the Catalan press.